My question is, given the general solution $$Y=C_1x+c_2\dfrac{1}{x}$$ find the differential equation

My attempt:

I have derivated the equation and then look for the constants:

$$Y'=C_1+c_2\dfrac{-1}{x^2}$$ $$Y''=c_2\dfrac{2}{x^3}$$

so $c_2=y''\dfrac{x^3}{2}$
and substitute in $y'$: $$c_1=y'+\dfrac{y''x}{2}$$
then $$y=(y'+\dfrac{y''x}{2})x+(y''\dfrac{x^3}{2})(\dfrac{1}{x})$$

and the equation its suppose to be


but when i solve it, it doesn't check with the general solution given, so, can someone please tell me what I'm doing wrong?



Given that $Y=C_1x+C_2\dfrac{1}{x}\implies xY=C_1 x^2+C_2$

Differentiating with respect to $x$,

$Y+xY'=2xC_1$ . . . . .$(1)$

Again differentiating with respect to $x$,

$Y'+Y'+xY''=2C_1\implies 2C_1=xY''+2Y'$

Putting the value of $2C_1$ in equation $(1)$ we have ,

$Y+xY'=x(xY''+2Y')\implies x^2Y''+xY'-Y=0$

This is the required differential equation.

If you want to cross-check the result, then take $$ x^2Y''+xY'-Y=0 \quad. . . . (2)$$

Putting $x=e^z\implies z=\log x$

Then $Y'=\frac{dY}{dx}=\frac{dY}{dz}\frac{dz}{dx}=\frac{1}{x}\frac{dY}{dz}\implies xY'=\frac{dY}{dz}=DY$(say), where $D\equiv \frac{d}{dz}$

similarly, $x^2Y''=D(D-1)Y$

Now from $(2)$,

$\{D(D-1)+D-1\}Y=0\implies (D^2-1)Y=0\implies Y=C_1 e^z+C_2e^{-z}\implies Y=C_1 x+C_2 \frac{1}{x}$

where $C_1$ and $C_2$ are arbitrary independent constants.

Hence the result holds.


Note that if $y_h=c_1x+c_2/x$ implies that $y_1=x$ and $y_2=1/x$ are solutions of: $$y''+P(x)y'+Q(x)y=0$$ Then \begin{cases} (y_1)'' + P(x)(y_1)' + Q(x)y_1=0 \\ (y_2)'' + P(x)(y_2)' + Q(x)y_2=0\end{cases} \begin{cases} 0+ P(x) + Q(x)x=0\implies P(x)=-xQ(x) \\ \frac{2}{x^3} -P(x)\frac{1}{x^2}+ Q(x)\frac{1}{x}=0\end{cases}

\begin{cases} 0+ P(x) + Q(x)x=0\implies P(x)=-xQ(x) \\ \frac{2}{x^2} -(-xQ(x)\frac{1}{x})+ Q(x)=0\end{cases} Then $$Q(x)=\frac{-1}{x^2}\implies P(x)=\frac{1}{x}$$ So $$y''+P(x)y'+Q(x)y=0$$ $$y''+\frac{y'}{x}-\frac{y}{x^2}=0$$ $$x^2y''+xy'-y=0$$


Note that $$ xy'=c_1x-\frac{c_2}x $$ which is the given solution up to a sign change. Thus repeating this combination of operations $$ x(xy')'=c_1x+\frac{c_2}x $$ returns the original solution. Thus the differential equation is $$ 0=x(xy')'-y=x^2y''+xy'-y. $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.